IMPROVING TEACHING METHODS USING DIGITAL TECHNOLOGY IN SCHOOL EDUCATION (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to show the diversity and complexity of the problem of choosing the most convenient resources for the teacher, to distinguish the main groups of digital tools and to propose their practical classification of digital resources. The article describes the improvement of resources and teaching methods intended for teachers of general education schools to carry out professional activities in the classroom.